Views of continuity and change: the Press Photo Archives in Buea, Cameroon. Issue 1 (2nd January 2018) - Schneider, Jürg
Abstract : The English-speaking part of Cameroon in the south western part of the country, two of a total of 10 regions and making up roughly 20% of the population, joined French Cameroun in 1961 to form the Federal Republic of Cameroon. In 1972, a new constitution replaced the federation with a unitary state called the United Republic of Cameroon. The Press Photo Archives in Buea, West Cameroon's former capital, is a remnant of this period. Covering a short but crucial period before independence as well as the process of the new independent state's formation and subsequent transformation into the Republic of Cameroon, the material of the Press Photo Archives and the Archives' institutional development grant, from an Anglophone perspective, a deep insight into this long and complex history. The photographs reflect continuity and change of state-wide rituals and the development of new iconographies as well as a challenged identity within the Cameroonian nation. However, the Archives not only store records of the past in a wide spectrum of topics but also the spectres of a contested past which needs to be controlled and appeased. The Press Photo Archives were an integral part of the Government Photographic Service which was created in 1955 by the British and continued its activities after independence as of part of the Ministry of Information and Culture and later the Ministry of Communication. The governmental photographers' duty was to follow any governmental or otherwise socially relevant events throughout the Anglophone regions of Cameroon.